2014
DOI: 10.5901/mjss.2014.v5n1p77
|View full text |Cite
|
Sign up to set email alerts
|

The Manifestation of Occupational Stress in the Teaching Profession: The Unheeded Voices of Teachers

Abstract: Numerous studies have established that teaching can be a stressful profession and that stress may affect career motivation and diminish effectiveness and job satisfaction of many loyal and gifted teachers. Van der Westhuisen (1991) observes that the increasing demands made on the schools and teachers have led to an alarming escalation of stress and professional burnout as career risks for those in the teaching profession. A major concern with occupational stress in the teaching profession is that prolonged ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 16 publications
2
13
0
4
Order By: Relevance
“…Furthermore, this study showed that poor job relationship was associated with WRS. Results from other studies support our results [24,54,59]. A possible reason could be that harmony and positive relationships between teachers may isolate stress triggers [60].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Furthermore, this study showed that poor job relationship was associated with WRS. Results from other studies support our results [24,54,59]. A possible reason could be that harmony and positive relationships between teachers may isolate stress triggers [60].…”
Section: Discussionsupporting
confidence: 91%
“…Working experience [19][20][21], job demands [22], educational level [19,20], job change [23], lack of support from co-workers, friends and family [23], and poor relationship with colleagues [24] were the most frequently reported factors as major work-related stressors.…”
Section: Introductionmentioning
confidence: 99%
“…Occupational stress has been claimed by some to be an unavoidable phenomenon of contemporary age ( Stojanović, Milenović, & Marković, 2012 ). Research has shown that teaching is a stressful profession, and that occupational stress can influence job satisfaction and motivation of teachers ( Maphalala, 2014 ). It may also enhance negative job attitudes ( Aquino & Thau, 2009 ; Barling, Kelloway, & Frone, 2005 ).…”
Section: Occupational Stressmentioning
confidence: 99%
“…According to Maphalala (2014) in his study on the manifestation of occupational stress in the teaching profession: the unheeded voices of teachers in South Africa, teaching stressors which the teachers found stressful, in order of most to least stressful, were curriculum changes, work load pressures, job insecurity, poor relationship with colleagues, reward and recognition, learners discipline problems, poor rapport with management and role ambiguity. In a research on factors contributing to the causes of work related stress and its impact on performance of teachers in Nkayi District, Zimbabwe, Ncube and Tshabalala (2013), found out that the major causes of stress among the respondents were poor pay, work overload, bad school management role overload and large class sizes.…”
Section: Synthesis Of Literature Unemployment Factors That Influence mentioning
confidence: 99%
“…In addition to this, the study also supports no significant difference in the marital status and occupational stress of secondary school teachers. Maphalala (2014) in his study on the manifestation of occupational stress in the teaching profession: the unheeded voices of teachers in KwaZulu Natal province, South Africa revealed that teaching stressors which the teachers found stressful, in order of most to least stressful, were curriculum changes, work load pressures and job insecurity. This study adopted a descriptive research design.…”
Section: Synthesis Of Literature Unemployment Factors That Influence mentioning
confidence: 99%